PELATIHAN MANAJEMEN KEUANGAN BAGI PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA TUMPUKRENTENG, KECAMATAN TUREN, KABUPATEN MALANG - Amad Sidi Pratomo; Muhammad Andi Fikri; Zaeniko Saputra; Khairunnisa (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
This community service is focused on Small, Micro, and Medium Enterprises (UMKM) in Tumpukrenteng Village, Turen District, Malang Regency. Business actors often lack understanding of financial management, especially financial and investment governance. So that the knowledge of UMKM actors in the financial sector needs to be improved so that there is no mismanagement in allocating and investing available funds. This encourages the importance of innovative financial management training with presentation, question and answer, and discussion methods to facilitate the absorption of knowledge. The method used in community service is the Asset Based Community Development (ABCD) method or Asset-Based Community Development as an approach used to see the condition of the community based on the assets and potentials owned in Tumpukrenteng Village. Overall, the training held in Tumpukrenteng village has a significant impact on UMKM actors in increasing their understanding of financial management as a provision for their business development.